(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Nadir DS. 2022. Effect of Aspergillus niger extract on production of coumarins in cell suspension cultures of Angelica archangelica. Biodiversitas 23: 5132-5138. Aspergillus niger is one of the most significant microbes employed in biotechnology and has been used for many years to make citric acid and extracellular enzymes. It is also utilized for waste treatment and biotransformation. In the last 20 years, A. niger has become a crucial transformational host to overexpress food enzymes. Different concentrations of A. niger extract were used to investigate their effects on the production of coumarin, both in the liquid medium and the cells, of batch cultures of Angelica archangelica L. Liquid Murashige and Skoog (MS) medium enriched with 2.0 mg.L-1 2,4-dichlorophenoxyacetic acid (2,4-D) combined with 0.5 mg.L-1 Kinetin (Kin), was used as growth medium for batch cultures of A. archangelica incubated for different incubation periods (7, 14 and 21 days). The results showed that 3.053 mg.g-1 was the highest coumarin concentration, obtained from the nutritional medium drawn from cultures treated with 2.0 mL.L-1 of A. niger after 21 days of incubation. However, 2.055 mg.g-1 was the maximum coumarin concentration reached in the harvested cells after 21 days of incubation when the cultures were treated with 2.0 mL.L-1 of A. niger extract. This study was aimed at performing extraction, identification, and estimation of coumarins from cell suspension cultures of A. archangelica and also investigating the effects of A. niger extract, at different concentrations, for various incubation periods on the production of coumarins. The concluded that A. niger extract affected coumarin accumulation, both in the medium and cells, from the cultures of A. archangelica. A dose of 2.0 mL.L-1 of A. niger extract as a biotic elicitor was found to have the best elicitor concentration, and that 21 days of incubation was the optimum period for the elicitor concentration to produce the highest coumarin content in batch cultures. Therefore, these results may contribute to increasing coumarin production by using different fungal extracts as biotic elicitors in cell suspension cultures.